Platelet genomics and proteomics in human health and disease - Macaulay, Iain C. (American Society for Clinical Investigation, 2005)
Proteomic and genomic technologies provide powerful tools for characterizing the multitude of events that occur in the anucleate platelet. These technologies are beginning to define the complete platelet transcriptome and proteome as well as the protein-protein interactions critical for platelet function. The integration of these results provides the opportunity to identify those proteins involved in discrete facets of platelet function. Here we summarize the findings of platelet proteome and transcriptome studies and their application to diseases of platelet function.